2021
DOI: 10.1183/16000617.0190-2020
|View full text |Cite
|
Sign up to set email alerts
|

Exertional ventilation/carbon dioxide output relationship in COPD: from physiological mechanisms to clinical applications

Abstract: There is well established evidence that the minute ventilation (V′E)/carbon dioxide output (V′CO2) relationship is relevant to a number of patient-related outcomes in COPD. In most circumstances, an increased V′E/V′CO2 reflects an enlarged physiological dead space (“wasted” ventilation), although alveolar hyperventilation (largely due to increased chemosensitivity) may play an adjunct role, particularly in patients with coexistent cardiovascular disease. The V′E/V′CO2 nadir, in particular, has been found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 141 publications
0
5
0
Order By: Relevance
“…In our study, an increased V ̇ E/V ̇ CO2 slope (i.e., ≥30), which is an indicator of ventilation/perfusion mismatch and overall worsening cardiopulmonary pathophysiology [22,23], was a predictor of mortality in the 42-month period in patients with COPD. There is evidence that the V ̇ E/V ̇ CO2 slope is relevant for a number of patient-related outcomes in COPD, as an increase in the V ̇ E/V ̇ CO2 slope reflects an increased physiological dead space [24]. Torchio et al [23] found that a V ̇ E/V ̇ CO2 slope ≥34 was related to a mortality risk of 5.5% and highlighted this variable for screening COPD patients who are candidates for pulmonary resection for potential ventilatory (Clinician's guide to cardiopulmonary exercise testing in adults: A scientific statement from the American heart association)failure.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, an increased V ̇ E/V ̇ CO2 slope (i.e., ≥30), which is an indicator of ventilation/perfusion mismatch and overall worsening cardiopulmonary pathophysiology [22,23], was a predictor of mortality in the 42-month period in patients with COPD. There is evidence that the V ̇ E/V ̇ CO2 slope is relevant for a number of patient-related outcomes in COPD, as an increase in the V ̇ E/V ̇ CO2 slope reflects an increased physiological dead space [24]. Torchio et al [23] found that a V ̇ E/V ̇ CO2 slope ≥34 was related to a mortality risk of 5.5% and highlighted this variable for screening COPD patients who are candidates for pulmonary resection for potential ventilatory (Clinician's guide to cardiopulmonary exercise testing in adults: A scientific statement from the American heart association)failure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, COPD patients are at high risk of developing insulin resistance via a TNF-α-mediated pathway [52,54]. However, it should also be considered that the interstitial fluid acidity due to elevated CO 2 level in COPD patients [55][56][57][58] would cause insulin resistance [12].…”
Section: Molecular Mechanisms Of Co-occurrence Of Insulin Resistance ...mentioning
confidence: 99%
“…Ventilatory efficiency (V̇ E /V̇CO 2 nadir and ΔV̇ E /ΔV̇CO 2 slope) : the relationship of V̇ E to V̇CO 2 has emerged as an important CPET outcome, reflecting disease severity, gas exchange inefficiency, and prognosis in both pulmonary 110 and cardiovascular 111 diseases. It is characterized either as the absolute ratio V̇ E /V̇CO 2 at its nadir shortly after GET ( Fig.…”
Section: Cardiopulmonary Exercise Testingmentioning
confidence: 99%